Investigation of genotoxic effects of doripenem using cytogenetic and molecular methods - Aydin, M.; Rencüzoğullari, E.; Bozkurt, O.; Genç, A.; Bayram, S. (Cellular and Molecular Biology, 2017)
The main aim of this study was to investigate the genotoxic effects of doripenem (DRP) using both cytogenetic and molecular test systems. Although there have been some studies reporting the effects of DRP, none of them has shown the genotoxic effects of DRP. In order to achieve the main aim of the study, the human peripheral lymphocytes were treated with 100 Î¼g/ml, 200 Î¼g/ml, and 400 Î¼g/ml concentrations of DRP for 24 and 48 hours, and the chromosome aberration (CA) and micronucleus (MN) methods were used as the cytogenetic tests and RAPD-PCR method was used as the molecular test to determine the genotoxic effects of DRP. DRP did not induce the chromosome aberrations and micronucleus frequencies at all concentrations and at all treatment periods. So, it was concluded that DRP did not show any cytotoxic effect. However, DRP increased the number of polymorphic bands and decreased the ratio of genomic template stability, especially at the 48-hour treatment period. In this study, according to the obtained results, it was determined that DRP failed to show any genotoxic risk at the therapeutic doses. This result also indicates that DRP could be a reliable antibiotics according to its rapid metabolism.